Role of Piperine in Cognitive Behavior and the Level of Nicotinic Receptors (nAChRs) in Mouse Brain - Chaiwiang, Narttaya; Pongpattanawut, Supawan; Khorana, Nantaka; Thanoi, Sutisa; Teaktong, Thanasak (Journal of Basic and Applied Pharmacology, 2016)
Piperine is an alkaloid found in black pepper and related plants, which has been used in traditional medicine for improving memory and learning. However, its mechanism of action remains unclear. The objective of this study was to investigate the role of piperine in modulating cholinergic function related to memory and learning in normal mice by using the Morris water maze (MWM) test, a behavioral tool commonly used to study spatial learning and memory. The results showed that repeated intraperitoneal injections of piperine at 5, 10, and 20 mg/kg/day for 2 weeks in mice decreased escape latency (11.00±1.05, 10.00±0.43 and 4.00±0.23 vs. 32.00±4.49 s, respectively) and increased retention time (32.00±0.73, 31.00±0.62 and 32.00±1.28 vs. 19.00±0.54 s, respectively) compared with controls. Significant increases in nicotinic acetylcholine receptor levels (nAChRs) in mouse brains of all piperine-treated groups were also observed (28.09±13.73, 19.55±2.60 and 18.20±2.13 vs. 15.97±3.04 fmol/mg, respectively; p<0.05). This indicates that the possible mechanism of action of piperine for improving cognitive function and memory in mice may involve increased brain nAChRs. These findings suggest that piperine might be useful for further development of compounds that improves learning and memory in patients with cognitive impairment.